Magnetic resonance imaging based computer‐guided dental implant surgery—A clinical pilot study. (9th September 2020) - Probst, Florian Andreas; Schweiger, Josef; Stumbaum, Maria Juliane; Karampinos, Dimitrios; Burian, Egon; Probst, Monika
Abstract: Background: Computer‐guided implant surgery is currently based on radiographic techniques exposing patients to ionizing radiation. Purpose: To assess, whether computer‐assisted 3D implant planning with template‐guided placement of dental implants based on magnetic resonance imaging (MRI) is feasible. Materials and methods: 3‐Tesla MRI was performed in 12 subjects as a basis for prosthetically driven virtual planning and subsequent guided implant surgery. To evaluate the transferability of the virtually planned implant position, deviations between virtually planned and resulting implant position were studied. Matching of occlusal surfaces was assessed by comparing surface scans with MRI‐derived images. In addition, the overall image quality and the ability of depicting anatomically important structures were rated. Results: MRI‐based guided implant surgery with subsequent prosthetic treatment was successfully performed in nine patients. Mean deviations between virtually planned and resulting implant position (error at entry point 0.8 ± 0.3 mm, error at apex 1.2 ± 0.6 mm, angular deviation 4.9 ± 3.6°), mean deviation of occlusal surfaces between surface scans and MRI‐based tooth reconstructions (mean 0.254 ± 0.026 mm) as well as visualization of important anatomical structures were acceptable for clinical application. Conclusion: Magnetic resonance imaging (MRI) based computer‐assisted implant surgery is a feasible and accurate procedure that avoids exposure to ionizing radiation.